A new species of Leptonema Guérin (Trichoptera: Hydropsychidae) from southeastern Brazil - Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2009)
The net-spinning caddisfly genus Leptonema Guérin contains about 120 species, making it the largest genus in the subfamily Macronematinae (Hydropsychidae) and one of the most diverse in the order Trichoptera (Flint et al. 1987; Flint 2008). Most species are large, with wingspans of about 60 mm. They inhabit all types of running waters and generally comprise a significant proportion of invertebrate biomass in these waterways (Flint et al. 1987). In the New World, the genus is extremely diverse, with 106 species widely distributed from the southwestern United States to northern Chile and central Argentina, including the Antilles (Flint 2008). Another 18 species occur in sub-Saharan Africa and Madagascar (Munõz-Quesada 1997). Flint, McAlpine & Ross (1987) revised the whole genus, and also considered biogeographic and phylogenetic aspects. Brazil has 26 recorded species (Paprocki et al. 2004; Flint 2008).